1996
DOI: 10.1016/0022-474x(95)00035-6
|View full text |Cite
|
Sign up to set email alerts
|

Alternative protection of cowpea seeds against Callosobruchus maculatus (F.) (Coleoptera: Bruchidae) using hermetic storage alone or in combination with Boscia senegalensis (Pers.) Lam ex Poir

Abstract: The effect of hermetic storage alone or in combination with Boscia senegalensis has been evaluated against Callosobruchus maculatus. Analysis of gas concentrations within a 7-day period indicated that O 2 declined from 19.2 to 2.3% and CO 2 rose from 1.2 to 22.8%. Prolonged storage durations increased adult mortality, significantly increased the developmental time and induced 60-80% reduction in the F1 progeny. The use of hermetic storage in combination with B. senegalensis fruits, at 1.2 g/1 (flask volume) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 12 publications
0
18
0
2
Order By: Relevance
“…Tanzubil (1991) found that C. maculatus could damage 100% of stored seed causing weight loss of up to 60%. After six months of storage, losses in terms of perforated seeds can reach 90% (ICRISAT, 1992;Seck et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Tanzubil (1991) found that C. maculatus could damage 100% of stored seed causing weight loss of up to 60%. After six months of storage, losses in terms of perforated seeds can reach 90% (ICRISAT, 1992;Seck et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In effect, cowpea production has gone a long way to cut down the problem of hunger in most parts of Africa. However, post-harvest losses usually caused by cowpea bruchids remain a key problem for many farmers [1,3,4]. The attack caused by cowpea weevil (Callosobruchus maculatus) has destroyed between 20 and 50% cowpeas on the continent each year, and in certain areas this loss could be up to 100% [5].…”
Section: Introductionmentioning
confidence: 99%
“…The action of the BPBs and WPBs could be compared to what happens when grains are stored in the Purdue Improved Cowpea Storage (PICS) bags [32]. Sealed PICS bags work, as do other hermetic storage containers, by excluding oxygen and raising the temperature of stored grains [54,55].…”
Section: Discussionmentioning
confidence: 99%